1997
DOI: 10.1073/pnas.94.23.12533
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic passive vaccination against chronic Lyme disease in mice

Abstract: Passive and active immunization against outer surface protein A (OspA) has been successful in protecting laboratory animals against subsequent infection with Borrelia burgdorferi. Antibodies (Abs) to OspA convey full protection, but only when they are present at the time of infection. Abs inactivate spirochetes within the tick and block their transmission to mammals, but do not affect established infection because of the loss of OspA in the vertebrate host. Our initial finding that the presence of high serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 61 publications
4
76
0
1
Order By: Relevance
“…As shown in Table 3, passive transfer of rabbit IS specific for ZS7.A68 and, with one exception each, also those with specificity for ZS7.A36 or ZS7.A66 into recipients before experimental challenge led to complete protection against disease and infection. Rabbit and mouse IS to OspC served as positive controls and normal rabbit serum as a negative control [11,20]. In essence similar results were obtained with mouse IS (data not shown).…”
Section: Immunogenicity Of Zs7a36 Zs7a66 and Zs7a68 During Infectsupporting
confidence: 67%
See 4 more Smart Citations
“…As shown in Table 3, passive transfer of rabbit IS specific for ZS7.A68 and, with one exception each, also those with specificity for ZS7.A36 or ZS7.A66 into recipients before experimental challenge led to complete protection against disease and infection. Rabbit and mouse IS to OspC served as positive controls and normal rabbit serum as a negative control [11,20]. In essence similar results were obtained with mouse IS (data not shown).…”
Section: Immunogenicity Of Zs7a36 Zs7a66 and Zs7a68 During Infectsupporting
confidence: 67%
“…), resulted in resolution of joint swelling and clearance of spirochetes. Previous experiments [11,20,22] and our initial experiments (data not shown) had already demonstrated that § 10 3 IS or normal mouse sera had no or only minimal effects on established B. burgdorferi infection in SCID mice.…”
Section: Immune Serum Raised Following Artificial Infection With Highmentioning
confidence: 53%
See 3 more Smart Citations